IMPACTS OF TECHNICAL ENVIRONMENT ON THE ADOPTION OF ORGANIC FERTILIZERS AND BIOPESTICIDES AMONG FARMERS: EVIDENCE FROM HEILONGJIANG PROVINCE, CHINA - Haoyue YANG, Ting MENG, Wojciech J. FLORKOWSKI (Frontiers of Agricultural Science and Engineering, 2023)
<ListItem><ItemContent> ● Farmer adoption of organic fertilizer and biopesticides was found to be positively correlated. </ItemContent></ListItem> <ListItem><ItemContent> ● The technical environment had a significant positive impact on farmers’ adoption of organic fertilizers and biopesticides. </ItemContent></ListItem> <ListItem><ItemContent> ● Technology training and local accessibility to new agricultural technologies enhanced both the adoption of organic fertilizers and biopesticides. </ItemContent></ListItem> <ListItem><ItemContent> ● Exchanging information about production techniques with others generally increased the likelihood of adopting organic fertilizers by 6%. </ItemContent></ListItem> Excessive application of mineral fertilizers and synthetic pesticides poses a substantial threat to the soil and water environment and food security. Organic fertilizer and biopesticides have gradually become essential technology for reducing mineral fertilizer and pesticide inputs. In the process, the technical environment is critical for promoting farmer behavior related to the adoption of organic fertilizer and biopesticides. This paper analyzes the influence of the technical environment on farmer behavior related to the adoption of organic fertilizer and biopesticides based on a survey of 1282 farmers in Heilongjiang Province, China, using the bivariate probit model. The results indicate that (1) farmer behavior related to the adoption applying organic fertilizer and biopesticides were positively correlated; (2) the technical environment had a significant positive impact on farmer behavior related to the adoption of organic fertilizer and biopesticides; and (3) the technical environment had a heterogeneous effect across different groups of farmers. This research provides insights useful for promoting organic fertilizer and biopesticides to farmers. It can be helpful to bundle relevant environmental technologies, conduct technology training for farmers and strengthen the construction of rural information networks.